Wastewater treatment process: a modified model for oxidation pond - Syafiqah Hanis, Mohd Fauzi (2021)
Wastewater treatment aims to eliminate suspended solids as many as possible before the remaining water, known as effluent, is released into the environment. Oxidation pond methods have practically been proven successful for the wastewater treatment process due to their low construction and maintenance costs. This study aims to investigate the degradation of wastewater pollutants through an oxidation pond treatment system. The purpose of this thesis is to present the relationship between the concentration of bacteria, which are phototrophic and coliform, chemical oxygen demand (COD), and dissolved oxygen (DO) in the form of modified mathematical model. Additionally, a Graphical User Interface (GUI) which predicting the wastewater treatment process in an oxidation pond is developed in this study. A modified model comprising of a set of ordinary differential equations (ODE) is proposed by incorporating Monod equation for COD. The model has been solved numerically by using the 4th order Runge-Kutta method and a parameter fitting technique namely Nelder-Mead simplex algorithm embedded in MATLAB software. To validate the result, a comparison between the model and the experimental data was carried out and measured by using the root mean squared error (RMSE). As a result, the modified mathematical model demonstrated lower RMSE as compared to the existing model. Since a lower RMSE value indicates better fit, the modified model provided a better approximation than an existing model based on the changes of the amount of concentration in the oxidation pond to produce good quality of water.